Antiviral effect of Archidendron pauciflorum leaves extract to hepatitis C virus: An in vitro study in JFH-1 strain (Faculty of Medicine Universitas Indonesia, 2018)
Background: Hepatitis C virus (HCV) is a leading cause of chronic liver diseases. Drug resistance to the regimen is also increasing. Hence, there is a need for new anti-HCV agents that are less toxic and more efficacious. The aim of this study is to evaluate theÂ possibility of A. pauciflorum extracts can be a antiviral drug.Methods: Huh-7it cells were infected with the HCV genotype 2a strain JFH-I in the presence of methanol extracts of Archidenron pauciflorum. The methanol extract further partition used n-hexane, ethyl acetate, n-butanol, and water showed in which butanol extracts exerted the strongest IC50 (6.3 g/ml). Further, the butanol fraction was fractionated and yielded into 13 fractions.Results: The methanol extract of the leaves of A. pauciflorum exhibited concentration dependent inhibition against the JFH1 strain of HCV genotype 2a with an IC50 is 72.5 Î¼g/ml. The butanol fraction exhibited the highest anti-HCV activity with an IC50 is 6.3 Î¼g/ml. The butanol fraction was fractionated which yielded 13 fractions. Fractions 5 and 13 exhibited high anti-HCV activities with IC50 is 5.0 Î¼g/ml and 8.5 Î¼g/ml and a time-of-addition study demonstrated that fraction 5 inhibited viral infection at the post-entry step, whereas fraction 13 primarily inhibited the viral entry step.Conclusion: The extract A. pauciflorum can be used as a herbal-based antiviral drug.